2017
DOI: 10.1051/0004-6361/201730772
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally-resolved UV photodesorption of CH4in pure and layered ices

Abstract: Context. Methane is among the main components of the ice mantles of insterstellar dust grains, where it is at the start of a rich solid-phase chemical network. Quantification of the photon-induced desorption yield of these frozen molecules and understanding of the underlying processes is necessary to accurately model the observations and the chemical evolution of various regions of the interstellar medium.Aims. This study aims at experimentally determining absolute photodesorption yields for the CH 4 molecule … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 65 publications
7
55
1
Order By: Relevance
“…Photodesorption mechanisms were studied for CH 4 and its daughter molecules. Dupuy et al (2017) found CH 4 photodesorption for monochromatic energies above 9.1 eV. However, in agreement with Cruz-Diaz et al (2014) and Martín-Doménech et al (2016), no evidence of a significant CH 4 photon-induced desorption was found in our work using the MDHL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Photodesorption mechanisms were studied for CH 4 and its daughter molecules. Dupuy et al (2017) found CH 4 photodesorption for monochromatic energies above 9.1 eV. However, in agreement with Cruz-Diaz et al (2014) and Martín-Doménech et al (2016), no evidence of a significant CH 4 photon-induced desorption was found in our work using the MDHL.…”
Section: Discussionsupporting
confidence: 91%
“…The direct desorption of a molecule from the ice surface (van Hemert et al 2015;Dupuy et al 2017), after absorption of a photon, is of low efficiency compared to the indirect photodesorption, by which the photon is absorbed by another molecule and the photon energy is distributed to the surrounding molecules. In this case, a UV photon can be absorbed by a molecule in the subsurface layers of the ice, leading to electronic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…CO photodesorption spectrum from H 2 CO:CO was also recorded. It looks like that from pure CO, except it is less intense but this is consistent with the fact that there is less CO at the surface of the mixed ice than in the thick pure ice of Dupuy et al 76 . As for the layered ice, these results illustrate how photodesorption depends on the ice composition and the thickness.…”
Section: Photodesorption Spectra Of Fresh H 2 Co Icessupporting
confidence: 82%
“…These studies have been reported for pure H2O (Cruz-Díaz et al (2017), and references therein), CO (Öberg et al (2007CO (Öberg et al ( , 2009b (2016)), CH4 (Dupuy et al (2017)), and NH3 (Nishi et al (1984); Loeffler & Baragiola (2010)) ices. In this work, we present a series of experiments simulating the UV photoprocessing of pure NH3 ices focused on the subsequent photodesorption of ice molecules.…”
Section: Introductionmentioning
confidence: 77%
“…This mechanism has been proposed by van Hemert et al (2015) for the photodesorption of CO molecules from a pure CO ice based on molecular dynamics simulations. However, in previous works this process had been proven to be inefficient during experimental simulations with CO and N2 ices when compared to indirect photodesorption mechanisms (see, e.g., Muñoz Caro et al (2010); Bertin et al (2012Bertin et al ( , 2013), although it may have a contribution in other cases (Dupuy et al (2017)). Alternatively, if the absorbing surface molecule photodissociates, the resulting photofragment can desorb provided that it is formed with enough kinetic energy, or it may recombine with another fragment, leading to the formation of a photoproduct that could also photodesorb thanks to the excess energy of the parent photofragments and/or the exothermicity released during the recombination reaction (see, e.g., Andersson & van Dishoeck (2008); Fayolle et al (2013);Fillion et al (2014); Bertin et al (2016)).…”
Section: Introductionmentioning
confidence: 98%